From microbe to metaphor: virus-like problems in organizations - Sleesman, Dustin J.; Cronin, Cory E. (Frontiers in Psychology, 2023)
Despite the important role of problem-solving in organizations, our understanding of the fundamental nature of problems is limited. To generate insights and discussion on this topic, we introduce the metaphor of a “virus-like” problem, which is a special kind of problem that often escapes the awareness of organizational leaders. Virus-like problems differ from other problems in organizations because, just like actual viruses, they are hidden, their source is difficult to identify, and they can quickly spread to others. Integrating the public health and organizational psychology fields, we draw lessons from the COVID-19 pandemic and how it was (mis) managed by public officials to offer a new perspective on problems in organizations and offer practical ideas for how leaders can address virus-like problems of their own.